New insights into SUMOylation and NEDDylation in fibrosis - Jin Han; Jin Han; Jun Wu; Wen-Tao Kou; Wen-Tao Kou; Li-Na Xie; Li-Na Xie; Ya-Li Tang; Ya-Li Tang; Da-Long Zhi; Da-Long Zhi; Ping Li; et al. (Frontiers Media S.A., 2024)
Fibrosis is the outcome of any abnormal tissue repair process that results in normal tissue replacement with scar tissue, leading to persistent tissue damage and cellular injury. During the process of fibrosis, many cytokines and chemokines are involved, and their activities are controlled by post-translational modifications, especially SUMOylation and NEDDylation. Both these modifications entail a three-step process of activation, conjugation, and ligation that involves three kinds of enzymes, namely, E1 activating, E2 conjugating, and E3 ligase enzymes. SUMOylation participates in organ fibrosis by modulating FXR, PML, TGF-β receptor I, Sirt3, HIF-1α, and Sirt1, while NEDDylation influences organ fibrosis by regulating cullin3, NIK, SRSF3, and UBE2M. Further investigations exhibit the therapeutic potentials of SUMOylation/NEDDylation activators and inhibitors against organ fibrosis, especially ginkgolic acid in SUMOylation and MLN4924 in NEDDylation. These results demonstrate the therapeutic effects of SUMOylation and NEDDylation against organ fibrosis and highlight their activators as well as inhibitors as potential candidates. In the future, deeper investigations of SUMOylation and NEDDylation are needed to identify novel substrates against organ fibrosis; moreover, clinical investigations are needed to determine the therapeutic effects of their activators and inhibitors that can benefit patients. This review highlights that SUMOylation and NEDDylation function as potential therapeutic targets for organ fibrosis.